Looking out for avian influenza in smallholding poultry flocks. (4th February 2022) - Welchman, David; Hansen, Rowena; Stephan, Lévon; Brzozowska, Anna
Abstract : This focus article has been prepared by David Welchman, Rowena Hansen, Lévon Stephan and Anna Brzozowska of the APHA. It is an update of a focus article first published in December 2017 ( VR, 9 December 2017, vol 181, pp 618–620).